Optical Absorption and Reflectivity of Four 2D Materials: MoS2, MoP2, NbS2, and NbP2 - Garcés, E.; Salas, O.; Magaña, L. F. (Frontiers in Materials, 2021)
We calculated the energy band structure and the optical absorption and reflectivity for each of the ultrathin 2D hexagonal materials MoS2, MoP2, NbS2, and NbP2. Our simulations included density functional theory, generalized gradient approximation (GGA), and the Quantum Espresso code. Other researchers already synthesized the first three materials. We obtained that NbP2 should be another hexagonal 2D material. In all cases in the infrared and visible ranges, the absorptions present much larger concerning graphene. However, the absorptions for MoP2, NbP2, and NbS2, are far more prominent concerning MoS2. In the ultraviolet region, the absorptions are like each other and differ from graphene. In all cases, the reflectivities are similar to each other and vary from graphene.